Research on the Transition Section Length of the Mixed Workface Using Gangue Backfilling Method and Caving Method - Tai Yang; Guo Shuai; Fang Kun (Open Geosciences, 2019)
Aiming at the problem of the sudden increase of the working resistance of the support in the transition section of the mixed workface, this paper adopts the physical simulation to study the fracture and movement characteristics of the overburden strata in the backfilling section and the caving section after analysis of the system layout of mixed workface. Then, the definition of the transition section of the mixed workface is given. Next, a numerical model of the transition section length is established based on the geological conditions of the Ji15-31010 mixed workface of Pingdingshan No.12 Coal Mine. In the numerical simulation, it is used to study the influence of the advancing length of the mixed workface and the length of the backfilling section on the transition section length. The results show that with the increase of the advancing length of the mixed workface and the decrease of the backfilling section length, the transition section length increases continuously and eventually stabilizes. The range of variation is 6.2~13.5 m, corresponding to 4~9 hydraulic supports with a width of 1.5 m. Based on the above conclusions and the price of transitional hydraulic supports, the 4 transitional hydraulic supports used in the transition section of the Ji15-31010 mixed workface is determined. Filed measurement shows that as the mixed workface is advanced from 10 m to 40 m, the transition section length increases from 2 supports to 4 supports, and decreases to 2 supports again when advanced to 60 m. This indicates that the main roof of the mixed workface between 40 and 60 m experiences the initial caving. The maximum length of the transition section is 6.0 m, corresponding to 4 hydraulic supports.